Baladewa Baladewa Studio in the Virtual Era: The Dynamics of Traditional Art Preservation in Digital Space: The Dynamics of Traditional Art - putra, anugrah; Hidajad, Arif (Solah, 2025)
Abstract: This study aims to examine in depth the dynamics of the activities of Sanggar Baladewa, a traditional art studio located in the city of Surabaya and focuses on the training and preservation of puppet and karawitan arts. This studio is a representation of efforts to preserve Javanese culture in the midst of a growing urban society. The COVID-19 pandemic situation that has hit since early 2020 has forced significant changes in the pattern of artistic activities, including activities carried out by Sanggar Baladewa. The transition to virtual space is a challenge as well as an opportunity that must be faced by a traditional art community like this. This research uses a library research method with a descriptive qualitative approach, which allows the exploration of data from various sources such as scientific journals, books, online articles, and documentation of studio activities. The focus of the analysis is directed at the adaptation strategies carried out by the studio in maintaining the existence of traditional art in the digital era. The results of the study show that although art activities can be transferred to an online format, this process is inseparable from a number of obstacles, including limited technological devices, uneven internet network access, and a decrease in the quality of artistic interaction between performers and audiences. However, Sanggar Baladewa continues to show high initiative and resilience in maintaining cultural practices through virtual performances. The use of social media and online video platforms such as YouTube is an alternative solution in delivering performances to the public. This adaptation is not only an effort to survive, but also opens up new possibilities in the spread of traditional arts to a wider society, including the younger generation who are more attached to digital technology. Thus, this study highlights the importance of strengthening the digital capacity of the traditional arts community and the need for synergy between art actors, educational institutions, and policy makers to support the sustainability of cultural heritage in the era of digital transformation. Keywords: Studio, Virtual, Pandemic, Traditional Arts, Karawitan, Cultural Adaptation